Sunday
March 26, 2017

Post a New Question

Posted by on .

if f(x) = (x/7)-3 find f^-1(x)

I'm completely lost! Help

  • CONFUSED~MATH - ,

    The inverse function f^-1(x) gives you back x when you input y = f(x) as the independent variable.

    Start with y = (x/7)-3
    y + 3 = x/7
    x = 7y + 21

    Since you are using x as the independent variable of the inverse function, you have to switch x and y in the equation above.

    The inverse function is therefore

    f^-1(x) = 7x + 21

    Check: Use (7x +21) as "x" in the f(x) equation, and you get x back.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question